# infinitude of inverses

###### Proposition 1.

Let $R$ be a ring with 1.

1. 1.

If $a\in R$$a$ has infinitely many right inverses.

2. 2.

If $a\in R$ has more than one right inverse, then $a$ has infinitely many right inverses.

###### Proof.
1. 1.

Let $ab=1$. Define $b_{0}=b,b_{1}=1-b_{0}a+b_{0},\dots,b_{i+1}=1-b_{i}a+b_{i},\ldots$ Then, by induction  , we see that $ab_{i}=a-ab_{i-1}a+ab_{i-1}=a-a+1=1$. Next we want to show that $b_{i}\neq b_{j}$ if $i\neq j$. Suppose $i>j$ and $b_{i}=b_{j}$. Again by induction, we have

 $b_{j}=b_{i}=1+(1-a)+\cdots+(1-a)^{i-j-1}+b_{j}(1-a)^{i-j}$ (1)

If we let $c=1+(1-a)+\cdots+(1-a)^{i-j-1}$ then $(1-a)c=c(1-a)=(1-a)+(1-a)^{2}+\cdots+(1-a)^{i-j}=c-1+(1-a)^{i-j}$. So Equation 3 can be rewritten as $c=b_{j}-b_{j}(1-a)^{i-j}=b_{j}(1-(1-a)^{i-j})=b_{j}ca$. Then $cb_{j}=b_{j}cab_{j}=b_{j}c$. Now, note that for $m\leq n$, $(1-a)^{n}b_{j}^{m}=(1-a)^{n-m}(b_{j}-1)^{m}$. This implies that

 $\displaystyle c{b}_{j}^{\phantom{j}i-j-1}$ $\displaystyle=$ $\displaystyle{b}_{j}^{\phantom{j}i-j-1}+(b_{j}-1){b}_{j}^{\phantom{j}i-j-2}+% \cdots+(b_{j}-1)^{i-j-1}$ $\displaystyle=$ $\displaystyle g(b_{j})+(b_{j}-1)^{i-j-1}.$

On the other hand, we also have

 $\displaystyle c{b}_{j}^{\phantom{j}i-j-1}$ $\displaystyle=$ $\displaystyle b_{j}c{b}_{j}^{\phantom{j}i-j-2}$ $\displaystyle=$ $\displaystyle b_{j}({b}_{j}^{\phantom{j}i-j-2}+(b_{j}-1)^{i-j-3}+\cdots+(1-a)(% b_{j}-1)^{i-j-2})$ $\displaystyle=$ $\displaystyle g(b_{j})+b_{j}(1-a)(b_{j}-1)^{i-j-2}.$

So combining the above two equations, we get $(b_{j}-1)^{i-j-1}=b_{j}(1-a)(b_{j}-1)^{i-j-2}$. Let $d=(b_{j}-1)^{i-j-2}$, then $(b_{j}-1)d=b_{j}(1-a)d=b_{j}d-b_{j}ad$. Simplify, we have $d=b_{j}ad$. Expanding $d$, then

 $\displaystyle{b}_{j}^{\phantom{j}i-j-2}+\cdots+(-1)^{i-j-2}$ $\displaystyle=$ $\displaystyle(b_{j}a)({b}_{j}^{\phantom{j}i-j-2}+\cdots+(-1)^{i-j-2})$ $\displaystyle=$ $\displaystyle b_{j}a{b}_{j}^{\phantom{j}i-j-2}+\cdots+b_{j}a(-1)^{i-j-2}$ $\displaystyle=$ $\displaystyle{b}_{j}^{\phantom{j}i-j-2}+\cdots+(-1)^{i-j-2}b_{j}a.$

Then $1=b_{j}a$ and we have reached a contradiction   .

2. 2.

For the next part, notice that if $b$ and $c$ are two distinct right inverses of $a$, then neither one of them can be a left inverse of $a$, for if, say, $ba=1$, then $c=(ba)c=b(ca)=b$. So we can apply the same technique used in the previous portion of the problem. Note that if $b_{j}a=1$, then

 $1=b_{j}a=(1-b_{j-1}a+b_{j-1})a=a-b_{j-1}a^{2}+b_{j-1}a.$

Multiply $b_{j-1}$ from the right, we have

 $b_{j-1}=ab_{j-1}-b_{j-1}a^{2}b_{j-1}+b_{j-1}ab_{j-1}=1-b_{j-1}a+b_{j-1}$

Thus $b_{j-1}a=1$. Keep going until we reach $ba=1$, again a contradiction.

Title infinitude of inverses       InfinitudeOfInverses 2013-03-22 18:17:30 2013-03-22 18:17:30 CWoo (3771) CWoo (3771) 4 CWoo (3771) Theorem msc 16U99